English Language Teaching: Approaches, Challenges, and Pedagogical Implications in Modern Education - Pauzan Pauzan (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
English language teaching (ELT) continues to develop in response to globalization, technological advancement, and evolving educational demands. This study aims to explore major approaches in ELT, examine challenges faced by educators and learners, and identify pedagogical implications for improving instructional practices. The study employs a qualitative literature review design by analyzing recent scholarly publications from 2022 to 2024 obtained from reputable academic databases. The findings indicate that Communicative Language Teaching, Task-Based Language Teaching, and Technology-Enhanced Language Learning play significant roles in promoting communicative competence, learner engagement, and autonomy. In addition, learner-centered instruction and the integration of digital technology provide broader opportunities for meaningful interaction and access to authentic learning resources. However, the effectiveness of these approaches is influenced by several challenges, including large class sizes, limited resources, diverse learner proficiency levels, and unequal access to technology. The study concludes that effective ELT requires the balanced integration of appropriate pedagogical approaches, technological support, and adaptive teaching strategies to address contextual classroom conditions and enhance overall learning outcomes. Keywords: English language teaching, communicative competence, language pedagogy, digital learning, language education